Translating Computer Abbreviations from English into Spanish: Main Types and Problems - Belda Medina, José (Meta, 2004)
AbstractMany computer terms have entered the Spanish language in recent years. Some of them are widely adopted without any previous modification. The number of English computer abbreviations used in Spanish is constantly increasing. Some of them are well-established, e.g. RAM, ROM, PC, but others have appeared very recently, e.g. WWW, ISP, IRC, HTML. This paper is intended to classify the different types of English abbreviations most commonly used in computer terminology and to identify the most important problems for their translation into Spanish as well as provide some solutions for it.